-x+42=4x

Simple and best practice solution for -x+42=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+42=4x equation:


Simplifying
-1x + 42 = 4x

Reorder the terms:
42 + -1x = 4x

Solving
42 + -1x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
42 + -1x + -4x = 4x + -4x

Combine like terms: -1x + -4x = -5x
42 + -5x = 4x + -4x

Combine like terms: 4x + -4x = 0
42 + -5x = 0

Add '-42' to each side of the equation.
42 + -42 + -5x = 0 + -42

Combine like terms: 42 + -42 = 0
0 + -5x = 0 + -42
-5x = 0 + -42

Combine like terms: 0 + -42 = -42
-5x = -42

Divide each side by '-5'.
x = 8.4

Simplifying
x = 8.4

See similar equations:

| -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 | | 5(n+2)+10=20 | | (6x^3-3x^2+4x)-(4x^2+3x+8)= | | 2x/3+20=30 | | 3(x-2)-x=12+5x | | -2/9r=-8 | | 4p-5=20 | | 2/3x-7/12x=5 | | 2y-6=4(y-2) |

Equations solver categories